2015
DOI: 10.1007/s40291-015-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lung Cancer by SHOX2 Gene Methylation Assay

Abstract: Lung cancer is the most prevalent cancer in the world. Few effective and cheap methods are available so far for early detection and screening of lung cancer. Although histological and cytological examinations are gold standards in lung cancer diagnosis, patients are always at late stages when diagnosis is confirmed. Therefore, new diagnostic methods are needed urgently to increase the early diagnostic rate, enhance the confirmed diagnostic rate, and reduce mortality. The SHOX2 gene methylation assay has become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
(94 reference statements)
0
18
0
Order By: Relevance
“…This study aimed at designing an IC system for bisulfite-based methylation qPCR assay in order to simultaneously and quantitatively monitor the DNA recovery and bisulfite conversion efficiencies, 2 parameters that are crucial for the accurate quantification of methylated targets. The IC designed here was validated in the context of quantifying the methylation status of SHOX2, known as a valuable biomarker in lung cancer detection (Darwiche et al, 2013;Song et al, 2015). The whole method was then validated on samples from patients with lung cancer and non-cancerous pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aimed at designing an IC system for bisulfite-based methylation qPCR assay in order to simultaneously and quantitatively monitor the DNA recovery and bisulfite conversion efficiencies, 2 parameters that are crucial for the accurate quantification of methylated targets. The IC designed here was validated in the context of quantifying the methylation status of SHOX2, known as a valuable biomarker in lung cancer detection (Darwiche et al, 2013;Song et al, 2015). The whole method was then validated on samples from patients with lung cancer and non-cancerous pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Four single-stranded synthetic oligonucleotides were designed, each containing CF sequence derived from the CFF (GRCh37:Chr13,19555120 -19555208) (Holmes et al, 2014), and CpG-containing sequence (named MP-SHOX2) of the SHOX2 promoter (GRCh38:Chr3,158103550 -158103675) (Song et al, 2015). All the cytosines (C) were converted to thymines (T) in two oligonucleotides (named ConIC-Oligos) but not converted in two others (named UnIC-Oligos).…”
Section: Construction Of the Ic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter methylation of tumor suppressor genes is common in body fluid and can be used as a lung cancer diagnosis method or biomarker. Several studies have evaluated its clinical application with acceptable diagnostic performance and high specificity …”
Section: Discussionmentioning
confidence: 99%
“… 22 24 It has been found that the SHOX2 gene includes two large CpG islands, one at the 5′ end, covering a region of approximately 1 kb, the other at the 3′ end, covering approximately 0.5 kb. 25 Studies have revealed that the methylation level of the SHOX2 gene CpG islands was significantly increased in tissues and cells of lung cancer compared with that from normal tissues and cells. 10 14 , 17 – 19 Growing evidence suggests that SHOX2 DNA methylation is a promising auxiliary diagnostic biomarker for lung cancer, but with considerable controversial results.…”
Section: Discussionmentioning
confidence: 99%